Iranian women’s experiences of infertility: A qualitative study - Nader Aghakhani; Béatrice Marianne Ewalds-Kvist; Fatemef Sheikhan; Effat Merghati Khoei (Shahid Sadoughi University of Medical Sciences, 2025)
Background: There are concerns and diverse experiences related to infertility and childlessness. The lived experience of infertile people from various cultures needs to be explored.
Objective: The aim of this qualitative study was to explore Iranian women experiences of their infertility.
Materials and Methods: The data comprised interviews about fertility issues in the Persian language with eighteen women, aged 17-45 yr old, who agreed to be interviewed at the Mottahari Infertility Treatment Clinic, affiliated to the Urmia University of Medical Sciences about their fertility problems. They were approached by the researchers at the time of their first visit. The verbatim transcribed interviews were analyzed using deductive conventional content analysis.
Results: The experiences of the informants were conceptualized into four major themes: 1) Shock (subthemes: Disbelief and Denial); 2) Reaction (subthemes: Distress, Guilt, Loss of self-esteem and Sexual reluctance); 3) Processing (subthemes: Internal processing, Avoidance, Marriage at risk, External processing, Stigma caused by the family and Stigma caused by the community) and 4) Reorientation (subthemes: Forgetting, Marriage to saving marriage and Sexual consent).
Conclusion: Infertility can be a challenging condition. Considering that infertility-related issues affect Iranian women more contextual factors is necessary. So, culturally sensitive and gender specific protocols are suggested to provide suitable and about culturally sensitive and gender-specific protocols is a necessity in order to provide suitable care to infertile women.